Automated Urinalysis for Evaluation of Microscopic Hematuria: Current Options and Revising the Gold Standard. Issue 3 (7th May 2020) - Hertz, Alexandria M.; Perez, Deo S.; Anderson, Mark I.; Brand, Timothy C.
Abstract : Introduction: Urinalysis is the defining test for microscopic hematuria and has traditionally been performed via microscopy. In recent years automated urinalysis machines, which use different technology to identify cells, have been widely adopted. There is little understanding of these machines in the urology community and how their use may affect evaluation of hematuria. Methods: We compared commercially available automated urinalysis machines and reviewed the literature comparing these machines to microscopic urinalysis. We also reviewed local hospital practices regarding these systems. Results: We identified 6 commercially available machines, almost all of which use flow cytometry as the mechanism to identify red blood cells. Review of the literature and local practice revealed differing definitions of normal range for red blood cells, most of which do not correlate with the American Urological Association definition of microscopic hematuria. There are also several methods for calibrating the machines in comparison to traditional microscopy. Conclusions: Use of automated urinalysis machines is widespread. However, these methods do not correspond exactly to traditional microscopy and use varying definitions of microscopic hematuria. These findings warrant additional investigation into the role of these devices in the definition of microscopic hematuria to prevent unneeded evaluations and to appropriately use health care resources.